MODEL PEMBELAJARAN PAI BERBASIS DIGITAL UNTUK PENGUATAN KARAKTER RELIGIUS: INTEGRASI PEMIKIRAN AL-FARABI, TEORI BANDURA, DAN BEHAVIORISME SKINNER: A Digital-Based Islamic Religious Education (PAI) Learning Model for Strengthening Religious Character: Integrating Al-Farabi’s Thought, Bandura’s Theory, and Skinner’s Behaviorism - Rasti Astuti Laisaan; Sita Acetylena (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Digital transformation in education has brought significant changes to the learning process, including in Islamic Religious Education (PAI). However, the use of technology in PAI instruction tends to focus on enhancing cognitive aspects rather than fully addressing the strengthening of students' religious character. This situation highlights the need to develop a digital-based PAI learning model that utilizes technology not merely as an instructional medium, but also as a means for internalizing values, fostering habits, and reinforcing character. This study aims to develop a conceptual model for digital-based PAI learning by integrating Al-Farabi’s educational thought, Albert Bandura’s social learning theory, and B.F. Skinner’s behaviorism. A qualitative approach utilizing library research methods was employed. Data were gathered through an examination of Al-Farabi’s major works, literature on Bandura’s and Skinner’s learning theories, and recent studies on the digitalization of Islamic education. Data analysis involved content analysis, comparative analysis, and conceptual synthesis. The findings indicate that Al-Farabi’s thought provides a philosophical foundation regarding the goal of education—shaping virtuous individuals on the path to happiness (sa‘ādah); the concept of al-takhyīl (imagination/representation) is relevant for development into "digital modeling" via visual and interactive media; and the concept of al-‘ādah (habituation) aligns with digital habituation through Skinner’s reinforcement mechanisms. Integrating these three perspectives yields a digital-based PAI learning model that combines digital modeling and digital habituation as strategies to strengthen religious character. This model asserts that digital technology functions not only as an instrument for knowledge transfer but also as an ecosystem for shaping students' religious values, attitudes, and behaviors.